Letter - Winstanley, E.
030-0213-001 Telegraphic Address, Inland - "Wholesale, Manchester." Foreign - "Copexport, Manchester." Telephone: Blackfriars 1212. Extension No. Please address your reply: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. Cable codes: A.B.C. 6th and 7th editions; Western Union 8 Letter; Bentley Complete Phrase; Bentley Second Phrase; A.I. Marconi, and private. Our reference EXPORT ST/HP. 345 Your reference 3rd February, 1938. Mr. Tewson, The Trades Union Congress General Council, Transport House, Smith Square, London. Dear Mr. Tewson, I have received your letter of the 2nd instant and am very pleased to learn that you have accepted our invoice for £37.12. 4. in respect of demurrage charges in connection with goods shipped by s.s. HARTBRIDGE. Your cheque for the amount in question has been duly received, and I have pleasure in enclosing herewith official receipt. Yours sincerely, E. Winstanley Export Department. 292/946/30/213